The influence of education on gender attitudes among ethno-religious majority and minority youth in Germany from a longitudinal perspective - Hakan Yücetas; Sarah Carol (Humanities and Social Sciences Communications, 2024)
It is well-known that exposure to education is related to egalitarian gender attitudes. Yet, previous studies did not sufficiently take the temporal variation of this relationship into account, especially regarding ethno-religious minority and majority adolescents in Europe. Adolescence represents crucial years for attitude development. We analyze the association between secondary education and gender attitudes of female and male youth belonging to the majority, Muslim, and non-Muslim minority in Germany by employing the CILS4EU-DE panel data with more than 3200 adolescents. Obtaining a secondary school degree is associated with more egalitarian gender attitudes in general. However, different patterns emerge for the various ethno-religious groups and for females and males. Particularly, the effect of secondary education in general is stronger for boys than girls, and upper secondary education is stronger for Muslim minorities than for majority youth. Thus, attitudes develop during adolescence, and education can lead to more egalitarian gender attitudes among some groups but not all equally.
Keywords: 370